PROCELOS: Giving priority to local cereals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Despite good crop yields the Sahel continues to import cereals to the detriment of its own farming. The availability of international suspluses of cereal products at relatively low costs, from the North, erratic crop yields in the South, the...